Physical Activity and Body Image Perceived by University Students during the COVID-19 Pandemic: A Systematic Review - Goicochea, Eliane A (2022)
Our objective was to assess the perception of body image and physical activity in university students during the COVID-19 pandemic. Of 74,270 papers found on 13 search engines between 12 August 2020, and 2 November 2021, we identified six studies (n = 1392 and 1097 were women). We found several results on the perception of both variables during the pandemic. First, physical activity tended to decrease or have negative changes, either because they dedicated less time to it, decreased the type of intensity or because they dedicated more time to sedentary activities. In addition, women were more physically active than men, since men perceived a decrease in their levels of physical activity. Secondly, there were also slight changes in the perception of body image; several students perceived that they gained weight and others had an increase in their BMI. It is even noted that those who were physically active or who were older in the population studied had a better perception of their actual physical condition. Similarly, we found that a concern for body image and even negative changes in the perception of appearance during confinement were reported. In conclusion, we found changes in the perception of physical activity and body image in college students during the COVID-19 pandemic.